Shareholder Gains During the Bank Merger Announcements in Malaysia - Lee, Miang Hua (2002)
This paper analyzes the shareholder gains surrounding the Malaysian bank merger announcements on 29th July 1999 and 14th February 2000. Initiated by the Bank Negara Malaysia (BNM) in the midst of financial crisis, the merger was not a market driven one in its real sense. In particular, this study measures the impact of these merger announcements on the appointed anchor bank, its target bank and combined bank. We find that all CARt are statistically insignificant at any conventional level regardless of the category during event window of 61-day and ll-day. We believe this is because these mergers are arranged by BNM and are not market driven. There are shareholder gains during the 11-day window for the combined bank category but the finding is not statistically significant. However, they show slight positive returns but not substantial during the 61-day window. We also find that the shorter periods ie. 11-day (-5,+5) would give higher level of CARt than longer periods ie. 61-day (-30,+30) in both initial and revised announcements. There are differences in CARt between the initial and revised announcements even though both announcements are arranged by BNM and involved the same banks. We believe that the differences are mainly due to greater flexibility being given to banks on merger during the revised announcement. There are also differences in cumulative abnormal returns among the categories namely anchor bank, target bank and combined bank during the 61-day window but for the event window 11-day, our finding conclude that there is at least one category of CARt which is similar with the other categories. For both event windows of 61-day and 11-day, CARt have a positive and statistically significant relationship with the relative shareholders' funds of the anchor bank (SHR) and New Anchor bank (NEW), and inverse relationship with the relative size of anchor to target banks (ASSET).